Schizophrenic urbanism: a quantitative approach for monitoring deviation in neighbourhood’s planning standards - Islam Sallam; Mohamed Faisal Al-Kazee (Journal of Architecture and Urbanism)
Urbanism represents a new terminology and a unique approach that describes and encounters the challenges of rapid urbanization in modern developments in contemporary cities and its effect on urban planning standards. As a metaphor, this term connects schizophrenia as a specific mental disease with precise features of urban planning, such as the loss of identity, place recognition, and community interaction with the social and environmental context. The lack of consensus adds a layer of complexity to understanding the subject matter. To add to the intricacy, schizophrenia has varied presentations with an unpredictable course and recovery. Symptoms of schizophrenia are divided into three broad categories: positive symptoms, negative symptoms, and recognition symptoms. This paper attempts to draw parallels between the recognition symptoms of schizophrenia and urban planning and gain an understanding as to whether urban planning and development are indeed schizophrenic in nature or whether the interference of local authorities, planners, and certain circumstances initiates a kind of deviations that leads to schizophrenic urban symptoms. This is done through an overview of the symptoms of schizophrenia and a comparison of specific symptoms with contemporary urban planning and development, focusing on fragmentation, disconnection from reality, identity loss, adaptability and change management, environmental interaction and conflict and tension. This will be done through critically analyzing contemporary urban planning and development in relation to disorganization and intervention. The study methodology is joined by locating turf within urban planning, sociology, and cultural assessments, and the ethnography research is used that contains interviews, surveys, and content analysis, to study the outcomes of plan requirements deviation and its impact on the local perception. The paper proposed coherent Key Performance Indicators KPIs that can estimate the consequences of applying international planning standards without acknowledging local diversity and place identity. This study encourages a culturally sensitive and locally inclusive approach to local neighborhoods’ planning principles, emphasizing the need to engage local communities in decision-making. The use of this proposed KPIs system could preserve and enhance the unique identities of neighborhoods and address their social needs amidst the challenges of rapid urbanization. The paper concludes that there is a high compatibility between the symptoms of schizophrenia and contemporary urban planning and development and that a greater understanding of schizophrenia can assist in improving the way we plan and develop cities’ neighbourhoods.